2018
DOI: 10.3390/polym10090972
|View full text |Cite
|
Sign up to set email alerts
|

Spinning Cellulose Hollow Fibers Using 1-Ethyl-3-methylimidazolium Acetate–Dimethylsulfoxide Co-Solvent

Abstract: The mixture of the ionic liquid 1-ethyl-3-methylimidazolium acetate (EmimAc) and dimethylsulfoxide (DMSO) was employed to dissolve microcrystalline cellulose (MCC). A 10 wt % cellulose dope solution was prepared for spinning cellulose hollow fibers (CHFs) under a mild temperature of 50 °C by a dry–wet spinning method. The defect-free CHFs were obtained with an average diameter and thickness of 270 and 38 µm, respectively. Both the XRD and FTIR characterization confirmed that a crystalline structure transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…As previously reported, the viscosity of the spinning dopes has a significant influence on the spinning process, and most of cellulose composite fibers were prepared by dry spray wet spinning with the concentration of spinning dope 8–12%. The concentration of spinning dope is 10% here, so that the viscosity of the spinning dope is not too high to ensure that the spinning can be carried out smoothly. The details of the preparation of MF/cellulose flame-retardant fibers are as follows: pre-MF and cellulose (polymerization degree: 550, mass ratio: 2:1) were dissolved in EmimDEP to form spinning dopes with solid content 10% at 70 °C.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, the viscosity of the spinning dopes has a significant influence on the spinning process, and most of cellulose composite fibers were prepared by dry spray wet spinning with the concentration of spinning dope 8–12%. The concentration of spinning dope is 10% here, so that the viscosity of the spinning dope is not too high to ensure that the spinning can be carried out smoothly. The details of the preparation of MF/cellulose flame-retardant fibers are as follows: pre-MF and cellulose (polymerization degree: 550, mass ratio: 2:1) were dissolved in EmimDEP to form spinning dopes with solid content 10% at 70 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Lei et al [83] used a microcrystalline cellulose (MCC) precursor to spun hollow fibers through a dry-wet spinning method, with a dope solution of 10 wt% of MCC with a co-solvent of 75 wt% EmimAc/25 wt% DMSO and a bore solution containing 20 wt% water/60 wt% EmimAc/20 wt% DMSO. From thermogravimetric analysis they concluded that produced MCC hollow fibers presented a pyrolysis behavior similar to deacetylated cellulose acetate.…”
Section: Selection Of Cellulosic Precursormentioning
confidence: 99%
“…The cellulose acetate precursor used by some authors has an average acetyl content of 40% [31,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. The direct carbonization of cellulose acetate membranes can form defects on the carbon matrix or even turn it into dust [31].…”
Section: Effect Of the Pre-treatmentsmentioning
confidence: 99%
“…Membranes utilizing ionic liquid as a solvent have been shown to perform in the ultrafiltration or nanofiltration regimes. This same ionic liquid approach was used to spin cellulose hollow fibers [12]. Cellulose membranes prepared using ionic liquid have been shown to be highly selective for organic dyes, rejecting 94% of Bromothymol Blue [13].…”
Section: Introductionmentioning
confidence: 99%